2003
DOI: 10.1002/jbm.a.10170
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of hyaluronan to metallic surfaces

Abstract: Metal implants are in general not compatible with the tissues of the human body, and in particular, blood exhibits a severe hemostatic response. Herein we present results of a technique to mask the surface of metals with a natural biopolymer, hyaluronan (HA). HA has minimal adverse interactions with blood and other tissues, but attachment of bioactive peptides can promote specific biological interactions. In this study, stainless steel was cleaned and then surface-modified by covalent attachment of an epoxy si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…20,21 HA, on the other hand, is a naturally occurring linear anionic polysaccharide present in advanced living organisms, with excellent lubricity, nonadhesive nature, and bacterial inhibitory effect. 22 It has been reported in an earlier work that a HA/ CH functionalized multilayer (with 10 bilayers deposited) on glass gave $80% reduction in the number of adherent E. coli. 23 Thierry et al reported that the HA/CH functionalized alloyed nickel-titanium (Ni-Ti) disks display good hemocompatibility with 38% reduction in platelet adhesion compared to unmodified Ni-Ti disks and a minimum of four bilayers were necessary to mask the metal substrate from its environment.…”
Section: Introductionmentioning
confidence: 97%
“…20,21 HA, on the other hand, is a naturally occurring linear anionic polysaccharide present in advanced living organisms, with excellent lubricity, nonadhesive nature, and bacterial inhibitory effect. 22 It has been reported in an earlier work that a HA/ CH functionalized multilayer (with 10 bilayers deposited) on glass gave $80% reduction in the number of adherent E. coli. 23 Thierry et al reported that the HA/CH functionalized alloyed nickel-titanium (Ni-Ti) disks display good hemocompatibility with 38% reduction in platelet adhesion compared to unmodified Ni-Ti disks and a minimum of four bilayers were necessary to mask the metal substrate from its environment.…”
Section: Introductionmentioning
confidence: 97%
“…Chitosan (CH) is a polycationic polysaccharide whose antibacterial properties [16,17] and osteoblast function-enhancing nature [18,19] have received substantial interest. Hyaluronic acid (HA), on the other hand, is a polyanionic polysaccharide present in advanced living organisms with excellent lubricity, non-adhesive nature and bacterial inhibitory effect [20]. Richert et al showed that HA/CH PEMs deposited with 10 bilayers on glass offered w80% reduction in the number of adherent Escherichia coli bacteria [21].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence microscopy was used to describe the uniformity of hyaluronan layers on stainless steel stents. 31 Fluorescence imaging was also useful to describe drug delivery in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%